An uncommon spontaneous right distal tubal pregnancy post bilateral laparoscopic sterilization: A case report. Issue 4 (January 2019) - Lin, Ching-Min; Ku, Yu-Lun; Cheng, Yu-Tzu; Giin, Ngo Yeh; Ou, Yu-Che; Lee, Meng-Chih; Lee, Chung-Yuan
Abstract: Rationale: Tubal sterilization as a contraception method has a high success rate; however, it also carries a low risk of incidental pregnancy. A majority of these pregnancies are ectopic. In this study, we report a rare case of spontaneous right distal tubal pregnancy after bilateral laparoscopic tubal sterilization. Patient concerns: A 36-year-old woman who had undergone bilateral laparoscopic tubal sterilization presented with abdominal pain and a positive test for pregnancy. Diagnosis: Ectopic pregnancy was suspected based on absence of gestational sac in the uterine cavity on ultrasound and elevated beta-human chorionic gonadotropin (β-hCG) level. Intervention: Since the patient had unstable vitals, emergency laparoscopic surgery was performed, which revealed a right distal fallopian tube pregnancy. We performed a complete bilateral residual tubal stump excision. Outcomes: The patient recovered well after surgery, with a reduction in β-hCG level, and was discharged after 3 days. Lessons: To ensure complete sterilization, the gap at the excised end needs to be adequately widened and enhanced with electro-destruction to prevent formation of a fistula.